1999
DOI: 10.1046/j.1525-1373.1999.d01-138.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Estrogen and Progestins on LDL Oxidation and Vascular Wall Cytotoxicity: Implications for Atherogenesis

Abstract: Estrogens are widely regarded as beneficial to arterial wall health. Among the mechanisms of this benefit are antioxidant effects on LDL and the arterial wall. Because progestins oppose the effect of estrogen in several systems, we asked if progestins oppose the antioxidant effect of estrogen. To study this question, LDL and various female sex hormones were incubated alone and combined in the absence or presence of bovine aortic endothelial cells, placental trophoblast, or macrophages, and LDL oxidation and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…The addition of estrogens to a system of LDL oxidation mediated by copper showed an increase in the initiation time of LDL oxidation 26 . Several studies have shown the effect of the administration of estrogens on human LDL oxidation [50][51][52] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The addition of estrogens to a system of LDL oxidation mediated by copper showed an increase in the initiation time of LDL oxidation 26 . Several studies have shown the effect of the administration of estrogens on human LDL oxidation [50][51][52] .…”
Section: Discussionmentioning
confidence: 98%
“…In liver cells, cholesterol is transformed into bile acids, which, in turn, are excreted in bile. Under the influence of estrogens, the following events may occur: (i) plasma triglycerides increase due to an increase in VLDL production; (ii) LDL concentration is reduced due to an increase in the expression of LDL receptors; (iii) HDL is increased by 2 mechanisms: greater secretion of apolipoprotein A-1, and lower removal of its lipids, because estrogens lead to a reduction in hepatic lipase activity (revised by Zhu et al 26 ).…”
Section: Total Oxysterolsmentioning
confidence: 99%
“…During last decades, researchers hypothesized that menopause itself represents an important threat to women's health because it is accompanied by increased systemic OxS, triggered by the loss of E2 which has antioxidant activity in vitro on cell cultures, ex vivo and in animal models [14,[69][70][71][72][73][74]. The hypothesis of a protection by E2 against oxidative damage to cardiovascular, neuronal and bone tissue still waits a definitive scientific validation in human disease since epidemiologic studies failed yet to confirm the in vivo impact of these hormones in the systemic redox balance, as we discuss below.…”
Section: Estrogen Decline and Increase In Disease Incidence The Rolementioning
confidence: 99%
“…Moreover, progestins have been reported to impair the cardioprotective effects of estrogen, as well as decrease serum NO levels and increase of plasma NO metabolites; nitrate and nitrite, even in the presence of high concentrations of 17b-estradiol [17]. Estrogen increases HDL-C whereas progestins can induce HDL-C levels fall in association with an increase in hepatic lipase activity.…”
Section: Discussionmentioning
confidence: 99%